تداخل ظاهرة الهجرة غير الشرعية بجريمة الاتجار بالبشر: واقع وتحديات - ابن حليلو، فيصل; حسن، أحمد محمد (جامعة الشارقة, 2020)
تعد ظاهرة الهجرة غير الشرعية من المشاكل الخطيرة التي تواجه المجتمع الدولي برمته، والتي تتطور مع تطور العلاقات بين الدول؛ حيث كانت الهجرة قديما في ذلك عدم وجود تنظيمات سياسية تبسط سلطتها على إقليم معين وتنظم عملية الدخول والخروج إليه، ومن ناحية أخرى، يعتبر الاتجار بالبشر ظاهرة دولية تمتد بين العديد من الدول المختلفة، وتختلف صورها وأنماطها من دولة لأخرى بحيث تشمل على سبيل المثال:[الاتجار بالنساء والأطفال لأغراض الدعارة والاستغلال الجنسي وبيع الأعضاء البشرية و....، وتمارسها عصابات الجريمة المنظمة وتدر أرباحا خيالية لهذه المنظمات الإجرامية المنظمة على حساب الحط من كرامة الإنسان وإيذانه جسدنا ونفسيا. ويهدف هذا البحث إلى تبيان واقع الهجرة غير الشرعية وأثرها على انتشار جريمة الاتجار بالبشر دوليا، وبيان حقوق المهاجرين غير الشرعيين كضحايا لجريمة الاتجار بالبشر، وبيان كيفية التصدي لجريمة الاتجار بالبشر الناتجة عن ظاهرة الهجرة غير الشرعية من خلال تناول الاتجار بالبشر في بروتوكول منع وقمع ومعاقبة الاتجار بالبشر وخاصة النساء والأطفال، (بروتوكول بالريمو 2000) المكمل لاتفاقية الأمم المتحدة لمكافحة الجريمة المنظمة عبر الوطنية وبروتوكول مكافحة تهريب المهاجرين، وبيان دور دولة الإمارات في مكافحتها لهذه الظاهرة، ومدى تطابق القانون الإماراتي بالاتفاقيات الدولية، لا سيما بروتوكول باليرمو وبروتوكول مكافحة تهريب المهاجرين.
The phenomenon of illegal immigration is one of the serious problems facing the international community as a whole, a phenomenon that develops with the development of relations between countries. Formerly, and in the absence of political organizations, immigration used to take over a particular region and control the entry and exit process. On the other hand, human trafficking is an international phenomenon that concerns many countries, and its images as well as patterns differ from one country to another. Such crimes include: trafficking in women and children for prostitution, sexual exploitation, sale of human organs, and other crimes organized by gangs which generate a lot of profit for these criminal organizations, while undermining human dignity and causing physical and psychological harm. This research aims to clarify the reality of illegal immigration and its impact on the international proliferation of the crime of human trafficking, and to elucidate the rights of illegal immigrants as victims of the crime of human trafficking. This is added to explaining how to address the crime of human trafficking resulting from the phenomenon of illegal immigration through studying human trafficking in the Palermo Protocol of 2000 regarding the prevention, suppression and punishment of human trafficking, especially women and children. It is worth noting that this protocol complements the United Nations Convention against Transnational Organized Crime and the Protocol against the Smuggling of Migrants. The study also sought to explain the role of the UAE in combating this phenomenon, and the extent to which UAE law is in line with international conventions, especially the Palermo protocol and the Protocol against the Smuggling of Migrants.
Keywords: القضايا الاجتماعية -- الهجرة غير الشرعية -- الاتجار بالبشر